La práctica docente y su incidencia en el aprendizaje significativo de los estudiantes de bachillerato general unificado de la Unidad Educativa “Ercilia de Martínez” del cantón Valencia, provincia de Los Ríos, año lectivo 2014 - 2015, Plan de capacitación para docentes. - Pastuña Chicaiza, Juan Santiago (2015)
This research was conducted in the Ercilia Martinez Education Unit, located in the canton Valencia, with Ministerial Decree no. 00482 dated January 4, 1986, the overall objective seeks to assess the impact of teaching practice in meaningful learning General high school students Unified Education Unit "Ercilia Martinez" Valencia Canton. In scientific research, inductive, deductive, descriptive and explanatory methods were used; and direct observation techniques, as constructivist principles used by teachers and the methodology employed; through a questionnaire data were collected, the director interviewed for more open responses opinion about the problem, photography, applied to the back of the existing information. The population was 405 people, to determine the sample formula was used with 95% probability, leaving one officer, 16 teachers, 131 students and 130 parents. The interview with the rector of the educational unit said it has no budget and depending on the district-12D06. And with regard to the teachers knew that there was a manifest failure to apply unsuitable by teachers teaching strategies, it has generated that students feel discouraged. The results of the surveys of students of the educational unit "Ercilia Martinez", 44% said that the teaching strategies applied by the teacher in the teaching-learning process in the various subjects is regular and 51% qualifying for nothing coordinated between theory and practice, this shows that teachers should bring harmony to ensure meaningful student learning. Teachers 38% prepare their lessons in advance, this is due to the many activities carried out or having experience in the field.